2021
DOI: 10.18231/j.ijmr.2021.042
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic use of natural phage cocktail for plants and potential for human applications

Abstract: Phages targeting specific bacteria have been used for control of bacterial pathogens in plants and humans. We report results of prophylactic use of a natural cocktail of phages on plants. Water was collected from upper reaches of the Alaknanda river where more than 200 isolates of phages have been reported. The river water was collected in April 2020 before the onset of monsoons and stored with sediments. The water was sprayed twice weekly on spinach, cabbage and coriander plants. We did not isolate, identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Notably, phages and their encoded lytic proteins can efficiently infect planktonic bacteria, and various studies have reported the effectiveness of phage cocktails and lytic proteins for biofilm destruction [ 5 8 ]. Compared with individual phages, phage cocktails have more widespread applications owing to their broad effect against bacteria, including the clinical treatment of multidrug-resistant bacterial infections and the control of multiple bacterial infections in poultry products, food, and sewage systems [ 9 12 ]. Lytic proteins encoded by phages, such as endolysins [ 13 ], holins [ 14 ], and depolymerases [ 15 ], act on the bacterial peptidoglycan skeleton and cell membrane.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, phages and their encoded lytic proteins can efficiently infect planktonic bacteria, and various studies have reported the effectiveness of phage cocktails and lytic proteins for biofilm destruction [ 5 8 ]. Compared with individual phages, phage cocktails have more widespread applications owing to their broad effect against bacteria, including the clinical treatment of multidrug-resistant bacterial infections and the control of multiple bacterial infections in poultry products, food, and sewage systems [ 9 12 ]. Lytic proteins encoded by phages, such as endolysins [ 13 ], holins [ 14 ], and depolymerases [ 15 ], act on the bacterial peptidoglycan skeleton and cell membrane.…”
Section: Introductionmentioning
confidence: 99%